ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN PARIWISATA HALAL DI KABUPATEN RAJA AMPAT, PROVINSI PAPUA BARAT - Saputra, Eko; Hafidhudin, Didin; Ayuniyyah, Qurroh (Universitas Ibn Khaldun Bogor, 2024)
Raja Ampat is a popular tourist destination known for its stunning natural beauty and rich biodiversity. The area's strong adherence to Eastern culture makes it a promising candidate for Halal Tourism, in addition to its existing reputation as a marine tourism hotspot. The study utilized field research with a qualitative approach, drawing on both primary and secondary data sources. The author reached three key conclusions: Firstly, from an Islamic perspective, tourism can be a way to appreciate the greatness of Allah and His creation. Muslim tourists are encouraged to uphold their religious practices, such as prayer and dietary restrictions, even while traveling. Secondly, Raja Ampat shows potential as a Halal Tourism destination, with a favorable Global Muslim Travel Index (GMTI) score of 41 out of 87. However, infrastructure development is needed to further enhance its attractiveness to Muslim travelers. Lastly, the study suggests four strategic steps to unlock Raja Ampat's Halal Tourism potential. These include strengthening Islamic historical tourism and the Sasi Tradition, promoting the concept of Halal Tourism, improving local education, ensuring tourist satisfaction, and addressing concerns and misconceptions through education and outreach efforts. In conclusion, Raja Ampat's unique cultural heritage and natural beauty position it as a promising player in the Halal Tourism market, provided that strategic steps are taken to enhance infrastructure and raise awareness among tourists and the local community about the concept of Halal Tourism.